Predictive role of BRAF mutations in patients with advanced colorectal cancer receiving cetuximab and panitumumab: A meta-analysis. Issue 5 (March 2015) - Pietrantonio, Filippo; Petrelli, Fausto; Coinu, Andrea; Di Bartolomeo, Maria; Borgonovo, Karen; Maggi, Claudia; Cabiddu, Mary; Iacovelli, Roberto; Bossi, Ilaria; Lonati, Veronica; Ghilardi, Mara; de Braud, Filippo; et al.
Abstract Background Wild type RAS (RAS-wt) status is predictive of the activities of the anti-epidermal growth factor receptor (EGFR) monoclonal antibodies cetuximab (C) and panitumumab (P). We examined the impact of C and P on progression-free survival (PFS), overall survival (OS) and overall response rate (ORR) in advanced colorectal cancer (CRC) patients who have RAS-wt/BRAF-mutant (BRAF-mut) status. Methods Randomised trials that compared C or P plus chemotherapy (or C or P monotherapy) with standard therapy or best supportive care (BSC) were included. We used published hazard ratios (HRs) if they were available, or we derived treatment estimates from other survival data. Pooled estimates of the treatment efficacy of anti-EGFR-based therapy with C or P for the RAS-wt/BRAF-mut subgroup were calculated with the random-effect inverse variance weighted method. All statistical tests were two-sided. Results Nine phase III trials and one phase II trial (six first-line and two second-line trials, plus two trials involving chemorefractory patients), that included 463 RAS-wt/BRAF-mut CRC patients, were analysed. Overall, the addition of C or P treatment in the BRAF-mut subgroup did not significantly improve PFS (HR, 0.88; 95% confidence interval (CI), 0.67–1.14; p = 0.33), OS (HR, 0.91; 95% CI, 0.62–1.34; p = 0.63) and ORR (relative risk, 1.31; 95% CI 0.83–2.08, p = 0.25) compared with control regimens. Conclusions C- or P-based therapy did not increase the benefit of standard therapy or the BSC in RAS-wt/BRAF-mut CRC patients. These findings support BRAF mutation assessment before initiation of treatment with anti-EGFR monoclonal antibodies.